Indo-Nepal Trade Relation: The Phenomenon of Black Hole Effect - Chaulagai, Mahesh K. (NRB Economic Review, 2014)
In the field of international trade, an economy is assumed to be reeling under the ’BLACK HOLE EFFECT’ originating from another economy, if all the major variables of international trade, irrespective of in which country they belong to, solely act in the favor of the latter economy. The results based on the models suggest that all the economic variables used in the study, whether Nepalese or Indian, show more favor to Indian economy compared to Nepalese economy confirming that Nepal has been spiraling into the ’BLACK HOLE EFFECT’ originated from the Indian economy. Such an effect tends to be an everlasting phenomenon until and unless a substantially enough counterbalancing force is applied to nullify it. The ’BLACK HOLE EFFECT’ explains why Nepal has not been able to reap the benefit in trade with India that would have come from the ’locomotive effect’ of the robust growth of the Indian economy.